Analisa Perhitungan Pada Biaya Produksi dengan Metode Harga Pokok Pesanan di UMKM Iffa Cookies Sidoarjo - Alifiana Rahmawati; Novita Dwi Adeliyah; Chairil Anwar (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The importance of calculating production costs to determine selling prices, especially for MSMEs today. In the current era of MSME bussiness environment, there are increasingly more competitors In marketing. For this reason, there is a need for method the cost of product orders. Determining this price effectively requires a good understanding of the cost order. In this research, the research method uses qualitative. The aim of the research is to find out the calculation of brownies production costs using the cost price method ordered by MSMEs iffa cookies in order to determine the selling price. The entity is still using the simple method, not yet using The order method. The results show that there is a difference regarding the production costs of MSME Iffa Cookies are IDR 260,975 and the production costs resulting from the researcher’s analysis of IDR 300,975. This also shows that using the cost order method is correct in determining the price for selling products.